OpenGL 4 Shading Language Cookbook. - Wolff, David (Packt Publishing, 2013)
OpenGL Shading Language 4 Cookbook is a hands-on guide that gets straight to the point - actually creating graphics, instead of just theoretical learning. Each recipe is specifically tailored to satisfy your appetite for producing real-time 3-D graphics using the latest GLSL specification. This book is for OpenGL programmers looking to use the modern features of GLSL 4 to create real-time, three-dimensional graphics. Familiarity with OpenGL programming, along with the typical 3D coordinate systems, projections, and transformations is assumed. It can also be useful for experienced GLSL programme.